كتابة الوصية في الفقه الإسلامي وتطبيقاتها في شركة الصالحين ترستي: دراسة تقويمية مقاصدية - Faiz Hatim Hanapi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research deals with the topic of Islamic inheritance management according to Islamic jurisprudence from the Maqasidiyyah perspective. The study is divided into four areas: the concept of the will, its provision in Shariʻah Islamiyyah, and the writing of the will with the approval of As-Salihin Trustee. This study uses the inductive, descriptive and analytical methods by addressing the theory on the will, the writing and the maqasid from the verses of the Quran, the Hadiths and their explanations and other relevant Islamic references. The researcher examines the applications of writing the will in As-Salihin Trustee and describes its process and then compares with the rules of shariʻah as stated in Maqasid Shariʻah. The study concludes that As-Salihin Trustee is one of the specialized companies in the field of will preparation and inheritance and it is the first company with such expertise in Malaysia.